1995
DOI: 10.1007/bf01585993
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing constrained subtrees of trees

Abstract: Given a tree G = (V, E) and a weight function defined on subsets of its nodes, we consider two associated problems. The first, called the "rooted subtree problem", is to find a maximum weight subtree, with a specified root, from a given set of subtrees.The second problem, called "the subtree packing problem", is to find a maximum weight packing of node disjoint subtrees chosen from a given set of subtrees, where the value of each subtree may depend on its root.We show that the complexity status of both problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…When weights are assigned to the points of the convex geometry, the natural question of finding a convex set with maximum-weight arises. Particular subproblems are the closure problem [32], the maximum-weight subtree problem [1,24], the maximum-weight path-closed set [17], or in a more geometrical setting, some variants of the minimum kgons problem [11]. A more recent example is the problem of finding a maximum-weight convex set in a split graph [5].…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…When weights are assigned to the points of the convex geometry, the natural question of finding a convex set with maximum-weight arises. Particular subproblems are the closure problem [32], the maximum-weight subtree problem [1,24], the maximum-weight path-closed set [17], or in a more geometrical setting, some variants of the minimum kgons problem [11]. A more recent example is the problem of finding a maximum-weight convex set in a split graph [5].…”
Section: Previous Workmentioning
confidence: 99%
“…Here is our main result. The well-known problem of finding a maximum-weight connected subtree in a tree can be solved by selecting a vertex as "root", finding a maximum-weight subtree that contains the root, and iterating this procedure for all possible roots (see Wolsey et al [1]). In order to use a similar approach to solve Problem 1, we define a notion of root.…”
Section: The Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park and Park [14] and van de Leensel et al [15] describe inequalities obtained by lifting the cover inequalities for the knapsack problem. Aghezzaf et al [1] study the related problem of packing subtrees with cardinality constraints. The second related set is the (fixed-charge) flow set, which is the relaxation of for A = .…”
Section: Motivating Examplesmentioning
confidence: 99%
“…Two other examples are the intersection of forest and cover polyhedra (Gamble and Pulleyblank [ 1989]) and the intersection of tree and matching polyhedra (Hall and Magnanti [1992]). As another example, Barany, Edmonds, and Wolsey [1986] and Aghezzaf, Magnanti, and Wolsey [1992] have shown that the packing of certain polyhedra (to model rooted trees) produces an integer polyhedra. As we show in this paper, by combining integer polyhedra via forcing constraints as in the problem [P], we do not always create an integer polyhedron.…”
Section: Problem Definition and Overviewmentioning
confidence: 99%